Question
\[ \text{Find } 2011^2 - 2010^2 \text{?} \]
Ask by Cox Frank. in South Africa
Feb 08,2025
Real Tutor Solution
Tutor-Verified Answer
Answer
\( 2011^2 - 2010^2 = 4021 \)
Solution
Calculate or simplify the expression \( 2011^2 - 2010^2 \).
Calculate the value by following steps:
- step0: Calculate:
\(2011^{2}-2010^{2}\)
- step1: Calculate:
\(\left(2011+2010\right)\left(2011-2010\right)\)
- step2: Calculate:
\(4021\times 1\)
- step3: Multiply the terms:
\(4021\)
The result of \(2011^2 - 2010^2\) is 4021.
Reviewed and approved by the UpStudy tutoring team
Like
error msg
![](/pmw/light_bulb.png?etag=525fd69ac661e11754e2fc9f1b18a4ee)
![](/pmw/spiral_notepad.png?etag=abe3906b7558c543a7b30ba53a3b5a5b)
The Deep Dive
To find \( 2011^2 - 2010^2 \), we can use the difference of squares formula, which states that \( a^2 - b^2 = (a - b)(a + b) \). Here, let \( a = 2011 \) and \( b = 2010 \). First, calculate \( a - b \): \[ a - b = 2011 - 2010 = 1 \] Next, calculate \( a + b \): \[ a + b = 2011 + 2010 = 4021 \] Now, substituting back into the difference of squares formula gives us: \[ 2011^2 - 2010^2 = (2011 - 2010)(2011 + 2010) = 1 \times 4021 = 4021 \] Therefore, the result is: \[ \boxed{4021} \]